2011
DOI: 10.1038/bjc.2011.112
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15: a prognostic marker for recurrence in colorectal cancer

Abstract: Background:Growth differentiation factor 15 (GDF15) belongs to the transforming growth factor beta superfamily and has been associated with activation of the p53 pathway in human cancer. The aim of this study was to assess the prognostic value of GDF15 in patients with colorectal cancer (CRC).Methods:Immunohistochemistry and tissue microarrays were used to analyse GDF15 protein expression in 320 patients with CRC. In a subgroup of 60 patients, the level of GDF15 protein in plasma was also measured using a soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 46 publications
5
85
0
Order By: Relevance
“…In oral and colorectal cancers, several reports have similarly shown that a high expression of GDF15 shown by immunohistochemistry was associated with many tumorigenic factors. 30,43 These data indicate that GDF15 in the cancer microenvironment might serve as a factor of the tumor progression of human ESCC.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 94%
See 2 more Smart Citations
“…In oral and colorectal cancers, several reports have similarly shown that a high expression of GDF15 shown by immunohistochemistry was associated with many tumorigenic factors. 30,43 These data indicate that GDF15 in the cancer microenvironment might serve as a factor of the tumor progression of human ESCC.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 94%
“…43 A similar upregulation of GDF15 immunoreactivity was also reported in adenocarcinomas including colorectal, gastric, and prostate cancers. 30,34,44 Wang et al 42 also indicated that positive staining of GDF15 in ESCC tissues was mostly confined to the cytoplasm of ESCC cells with a diffuse pattern. In the present study too, the GDF15-positive cells in the ESCC tissues were mostly confined to the cytoplasm of ESCC cells, whereas GDF15 immunoreactions were detected in other stromal cells such as erythrocytes and macrophages.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 99%
See 1 more Smart Citation
“…165 GDF-15 has been investigated in other cancers, and high plasma levels correlated with reduced time to recurrence and reduced overall survival in colorectal cancer. 216 In ovarian cancer high level of GDF-15 in ascites was an independent predictor of poor survival 121 , and preoperative plasma levels an independent predictor of poor survival. 123 We have shown GDF-15 as an independent predictor of lymph node metastasis (Paper III).…”
Section: The Role Of Serological Biomarkers In Endometrial Cancermentioning
confidence: 95%
“…GDF15 is published as a prognostic biomarker in ovarian cancer [1], a marker for tumor recurrence in colorectal cancer [2], and a novel serum marker for metastasis in uveal melanoma [3]. GDF15 expression is rapidly induced by a variety of cellular stresses in a p53-dependent and -independent manner, and it mediates cell cycle arrest and apoptosis in response to DNA damage, toxins, anoxia, liver injury, and other cellular stresses in different models [4][5][6].…”
Section: Introductionmentioning
confidence: 99%